PENINGKATAN MOTIVASI BELAJAR MENGAJI MELALUI PROGRAM KULIAH KERJA NYATA (KKN) BERBASIS MASJID DI DESA DUSUN BARU II KECAMATAN KARANG TINGGI KABUPATEN BENGKULU TENGAH - Purwanti, Denada; Madyani, Fitri; Nur Qori'a, Nabila; Sintia Karunia, Nurika; Wulan Dari, Ikke (CV. Kalimasada Group, 2024)
The mosque-based Community Service Program (KKN) implemented in Dusun Baru II Village, Karang Tinggi District, Central Bengkulu Regency, aims to increase motivation to learn the Koran in the local community. This research highlights the implementation of the KKN program by students at Fatmawati Sukarno Bengkulu State Islamic University which involves activities such as interactive learning and technology-based training at mosques. Through surveys, in-depth interviews and field observations, the KKN team identified main problems, including low motivation to learn the Koran and limited educational facilities. Program implementation includes mutual cooperation activities, tahfiz classes, and support from family and community. Results showed a significant increase in interest in learning the Koran across all age groups, with 80% of children, 75% of teenagers and 60% of seniors reporting higher engagement. Support from the surrounding environment and the use of varied learning methods also contribute to the success of the program. This program has succeeded in improving the quality of religious learning and supporting the development of a more religious and harmonious community.